(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Corona viruses are a large family of viruses that cause illness ranging from the common cold to more severe diseases. A novel coronavirus (nCoV) is a new strain that has not been previously identified in humans. On 30 January 2020, the WHO Director-General declared the novel corona virus (COVID-19) outbreak a public health emergency of international concern. Many fatalities have occurred and continue to happen. Despite staggering research efforts for therapeutics, complete cure is still a distant dream. The write up updates the treatment approaches utilized in clinical settings across the globe and the clinical trials registered in the Federal register and WHO register for drugs and vaccines to combat the pandemic.